Characterisation of collective motion - Kjellman, Cecilia (My University, 2015)
Self-organisation and emergence is a widespread and fundamental aspect of biological systems. Fish schools, insect swarms, bird ocks, colonies of bac- teria and human crowds are familiar examples of systems of very different levels of complexity and scale. To determine what governs interaction in the many biological systems is of importance. This thesis mainly focuses on comparing information usage for modelling collective motion, comparing using the distance to neighbouring individuals and time to collision. The thesis begins with analysing gathered sh school data in light of recent work in the eld of human crowd behaviour. The method uses a pair distribution function and a possible interaction energy to compare the two characteristics distance to neighbouring individuals and time to collision. The result differs in an interesting way from the original article on human crowd behaviour. The later part of the thesis describes existing collective behaviour models, and model adjustments, using either distance or time to collision as the most important attribute. Suitable existing measurements are touched upon. Fi- nally simulations using the included models are discussed but no conclusion regarding any decisive variable is made.
Keywords: Annan naturvetenskap; Energi; Other Natural Sciences; Energy